Marriages Not Recorded Perspective Enakmen 8 Year 2004 State of Sabah and Marriage Law Number 1 Year 1974 - Yunitasari Yunitasari; Nihrul Bahi Al Haidar; Ita Ma’rifatul Fauziyah (Budapest International Research and Critics University, 2022)
Marriages that are not registered in perspective Ekamen 8 of 2004 in the State of Sabah and the Marriage Law No. 1 of 1974 is a normative study in order to answer two questions, namely: first, about the problem of what if a marriage is not registered while marriage is required to be registered, second, how is the analysis of a marriage that is not recorded the perspective of enactment 8 of 2004 and Law No. 1 of 1974. The data of this study were collected using the documentation method, then analyzed using a descriptive method, namely by using a deductive mindset. The results of this study conclude that if there is a marriage that is not registered then it violates the law and the perpetrator himself is subject to a fine of RM1000 (ringgit) or imprisonment for approximately 6 (six) months, as well as marriages that do not recorded in Indonesia, it will be subject to a fine of Rp. 7,500,000, - (Seven Million Five Hundred Rupiah). In line with the conclusions above, suggestions for the future should be further developed with research with the theme of marriage that is not recorded. And more mastering theories about his knowledge so that as a legal academic at least he can provide enlightenment or solve problems or cases that will occur in the future. will decrease, so that people will respect the applicable laws